First record of an epibiont protozoan Epistylis sp. (Ciliophora, Peritrichia) attached to Ergasilus chelangulatus (Ergasilidae) in Brazil - Azevedo,RK. (2014)
In the present paper, we described the first record of an epibiont protozoan Epistylis sp. Ehrenberg, 1830 (Ciliophora, Peritrichia) attached to Ergasilus chelangulatus Thatcher and Brasil-Sato, 2008, parasite of Pimelodus maculatus Lacépède, 1803 in Brazil, with electron microscope observations. Fish were collected in Veados River, state of São Paulo and the crustacean Ergasilus chelangulatus being registered for the first time in this river, expanding its geographical distribution in Brazil.